Experiences of aftermath of COVID-19 in relation to social, financial and health related aspects among previously hospitalized patients: a qualitative exploration - Nandonik, Ahmed Jojan; Das Pooja, Shangjucta; Ahmed, Tanvir; Parvez, Anwar; Kabir, Zarina Nahar (Frontiers in Public Health, 2023)
Background: There is increasing evidence of long-term consequences of COVID-19. The world has seen multidimensional impact of the pandemic and Bangladesh is no exception to that. Policymakers in Bangladesh laid out strategies to curb the initial spread of COVID-19. However, long-hauler-term consequences of COVID-19 received little or no attention in the country. Evidence suggests that people presumed to be recovered face multidimensional post-covid consequences. This study aimed to describe the aftermath of COVID-19 in relation to social, financial and health related aspects among previously hospitalized patients. Methods: This descriptive qualitative study includes participants (n=14) who were previously hospitalized for COVID-19 and returned home after recovery. The participants were part of a mixed method study from which they were purposively selected. Semi-structured in-depth interviews were conducted over telephone. Inductive content analysis was used to analyze the data. Results: Twelve sub-categories emerged from the data analysis which converged into five main categories. The main categories included perspective on physical health, financial struggle, life adjustment, interplay between different domains and spontaneous support. Conclusion: The lived experiences of COVID-19 recovered patients highlighted multidimensional impact on their daily lives. Physical and psychological wellbeing found to be related to the effort of restoring financial status. People’s perception about life altered due to pandemic, for few the pandemic was an opportunity to grow while others found it difficult to accept the hardship. Such multidimensional post COVID-19 impact on people’s lives and wellbeing holds considerable implication for response and mitigation plan for future related pandemics.